Analisis Perputaran Kas, Piutang Dan Persediaan Pada Usaha Berlian Pak Suhaimi Di Tenggarong - Ulfah, Siti; Palinggi, Yonathan; Erwinsyah, Erwinsyah (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2019)
Abstract:The purpose of this study was to determine and assess the level of cash turnover, accounts receivable and inventories in Pak Suhaimi's diamond business in Tenggarong for the period of 2016 - 2018.The average cash generated by Pak Suhaimi's Diamond Business in Tenggarong in 2016 was Rp. 23,777,050, in 2017 is Rp. 28,400,000 increased by Rp. 4,622,950 (19.4%) and average cash in 2018 amounting to Rp. 26,000,000 or decreased by Rp. 2,400,000 (8.4%). Cash turnover generated in 2016 amounted to 7.62, in 2017 decreased by 7.28 times and cash turnover in 2018 amounted to 6.63 times or decreased by 0.65 times. The cash turnover period generated in 2016 for 47 days, in 2017 is 49 days and the cash turnover period in 2018 is 54 days or 5 days longer.The average receivables generated at the Pak Suhaimi Diamond Business in Tenggarong in 2016 amounted to Rp. 23,830,000, in 2017 Rp. 36,805,000 or an increase of Rp. 12,975,000 (54.4%) and the average receivables in 2018 were Rp. 34,125,000 or decreased by Rp. 2,680,000 (7.2%) Receivables turnover generated in 2016 amounted to 7.60, in 2017 amounted to 5.61 times and accounts receivable turnover in 2018 was down by 5.05 times or decreased by 0.56 times. Receivables turnover period generated in 2016 for 47 days, in 2017 amounted to 64 days and receivables turnover in 2017 amounted to 71 days or 7 days later.The average inventory produced by Pak Suhaimi's Diamond Business in Tenggarong in 2016 was Rp. 26,000,000, in 2017 in the amount of Rp. 21,550,000 or down Rp. 4,450,000 (17.1%) and the average inventory in 2018 of Rp. 24,850,000 or increase to Rp. 3,300,000 (15.3%). Inventory turnover generated in 2016 amounted to 6.97, in 2017 amounted to 9.59 times and inventory turnover in 2018 amounted to 6.94 times or decreased by 2.65 times. Inventory turnover period generated in 2016 for 52 days, in 2017 amounted to 38 days and inventory turnover period in 2018 amounted to 52 days or no later than 14 daysBased on the analysis and discussion above, we can see that cash turnover, accounts receivable turnover and inventory turnover of Pak Suhaimi Diamond Business in Tenggarong in 2018 decreased when compared with the previous year 2017 and 2016. So that the proposed hypothesis was accepted because it was proven correctKeywords: Cash Turnover, Receivables, Inventory